2017
DOI: 10.1177/0885328217739562
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and in vivo evaluation of a novel gel-based wound dressing using arginine–alginate surface-modified chitosan nanofibers

Abstract: The development of an effective wound dressing with the ability to induce skin wound healing is a great challenge in medicine. Nanofibers are highly attractive for wound dressing preparation due to their properties such as hemostasis induction, good absorption of wound exudates, and facilitation of cell growth. Chitosan nanofibers have attracted great attention for application in wound dressings due to their accelerating effects on wound healing. In this study, arginine surface-modified chitosan nanofibers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 50 publications
(71 reference statements)
0
13
0
Order By: Relevance
“…The high viscosity property allows for the fibres to stay on the wound cavity instead of moving away in heavily exudated wounds. The fibres did not show any burst release, however, about 85% of arginine was release in 24 h and a wound closure of 93.8% ± 3.1 was observed after nine days [83]. The two studies above demonstrated the use of biocompatible polymers to fabricate biocompatible and cytocompatible BMPs with optimal properties.…”
Section: Ionic Gelation Technique Employed In Fabrication Of Chitosanmentioning
confidence: 88%
See 3 more Smart Citations
“…The high viscosity property allows for the fibres to stay on the wound cavity instead of moving away in heavily exudated wounds. The fibres did not show any burst release, however, about 85% of arginine was release in 24 h and a wound closure of 93.8% ± 3.1 was observed after nine days [83]. The two studies above demonstrated the use of biocompatible polymers to fabricate biocompatible and cytocompatible BMPs with optimal properties.…”
Section: Ionic Gelation Technique Employed In Fabrication Of Chitosanmentioning
confidence: 88%
“…An optimum cytocompatibility with the cell viability of 100.97% ± 0.071 and higher wound healing ratio was observed in the CS/Coll/Alg composite dressing treated rats than in the gauze or chitosan treated ones [48]. In an unrelated study, a similar concept in fibre preparation was employed; arginine surface-modified chitosan nanofibers were prepared by the attachment of arginine molecules on the surface of chitosan nanofibers using sodium alginate through electrostatic interaction [83]. The nanofibers had an average diameter ranging from 100 to 150 nm, and also showed high viscosity of 1000 cps [83].…”
Section: Ionic Gelation Technique Employed In Fabrication Of Chitosanmentioning
confidence: 99%
See 2 more Smart Citations
“…Alginates were modified with a cell adhesive GRGDSP oligopeptide, which acts as ligand for integrin cell adhesion receptors [43]. Sodium alginate was used for attachment of arginine to the surface of chitosan nanofibers in order to increase healing capability of this wound dressing [46]. Alginate nanofibers supported by PCL were impregnated with an extract from Spirulina, a photosynthetic cyanobacterium producing bioactive molecules with anti-oxidant and anti-inflammatory effects [45].…”
Section: Introductionmentioning
confidence: 99%